2023
DOI: 10.1101/2023.11.02.565362
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simplified post-assembly plasmid library amplification for increased transformation yields inE. coliandS. cerevisiae

Thomas Fryer,
Darian S. Wolff,
Max D. Overath
et al.

Abstract: Many biological disciplines rely upon the transformation of host cells with heterologous DNA, the limited efficiency of which can significantly hinder a researcher’s work. Directed evolution in particular typically requires the screening of large (thousand-billion member) libraries to identify sequences of interest, and the creation of these libraries at large enough scales to overcome transformation inefficiencies is a cost-and time-intensive process. We simplify this process by using Rolling Circle Amplifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In addition, they explored the potential scalability of chemical transformation performed in parallel on multiple samples and the use of increased cell volumes. The authors found that the most effective approach involved using a modified Inoue protocol [24].…”
Section: мікробіологія / Microbiologymentioning
confidence: 99%
“…In addition, they explored the potential scalability of chemical transformation performed in parallel on multiple samples and the use of increased cell volumes. The authors found that the most effective approach involved using a modified Inoue protocol [24].…”
Section: мікробіологія / Microbiologymentioning
confidence: 99%